Bacterial diversity and fatty acid composition of hypersaline cyanobacterial mats from an inland desert wadi. (April 2015) - Abed, Raeid M.M.; Klempová, Tatiana; Gajdoš, Peter; Čertík, Milan
Abstract: Hypersaline cyanobacterial mats are infrequently reported in desert streams and information on such mats is very scarce. We investigated bacterial diversity and fatty acid composition in hypersaline cyanobacterial mats from Wadi Muqshin, located inland near the Empty Quarter desert in Oman. Most of the detected cyanobacteria belonged to known halotolerant, thermotolerant and UV resistant types that were typically reported in other hypersaline mats. A total of 84, 834 ribosomal sequences were obtained, with 62–79% of the sequences affiliated to Cyanobacteria, Proteobacteria, Bacteroidetes, Clostridia and Chloroflexi . Cluster analysis showed that Mat 5 with the highest salinity was profoundly different from the other mats and shared species were ≤72% between all mats. While most Deltaproteobacteria in the wadi mats belonged to sulfate-reducing bacteria, a number of sequences related to purple sulfur, purple non-sulfur as well as green no-sulfur bacteria were also detected. Different saturated, branched and mono- and di-unsaturated fatty acids were detected in all mats, with the saturated 16:0 and 18:0 and the monounsaturated 16:1 and 18:1 fatty acids accounting for relative amounts of 70–77% of total fatty acids. We conclude that microbial diversity and fatty acids composition in the desert wadi hypersaline cyanobacterial mats resemble their counterparts from other hypersaline environments. Highlights: Hypersaline microbial mats in desert wadis have been rarely reported and studied. Wadi mats resemble their counterparts from other hypersaline environments. Typical hypersaline and UV-tolerant bacterial strains are detected in wadi mats. Fatty acids detected in wadi mats reflect their adaptation to desert environment.